The Efficacy of Fingolimod and Interferons in Controlling Disability and Relapse Rate in Patients with Multiple Sclerosis: A Systematic Review and Meta-Analysis - Shaygannejad, Vahid; Mirmosayyeb, Omid; Bagherieh, Sara; Shaygan, Parisa; Ghajarzadeh, Mahsa (International journal of preventive medicine, 2023)
Fingolimod and interferons are used in the relapse form of multiple sclerosis (MS). The goal of this systematic review and meta-analysis was to evaluate the efficacy of fingolimod versus interferon in patients with MS. The systematic search was done in PubMed, Scopus, Embase, Web of Science, and Google Scholar. The references of included studies as well as conference abstracts were searched up to July 2021. The literature search revealed 8211 articles, and after deleting duplicates 5594 remained. For the meta-analysis, four studies were included. The standardized mean difference (SMD) of the Expanded Disability Status Scale (EDSS) after treatment (interferon vs fingolimod) was -0.06 (95% CI: -0.28, 0.17) (I = 80.2%, = 0.002). The SMD of the annual relapse rate (ARR) after treatment (interferon - fingolimod) was -0.08 (95% CI: -0.53, 0.36) (I = 95.5%, < 0.001). The SMD of the ARR after treatment and before treatment in the interferon group was - 1.45, (95% CI: -1.55, -1.36) (I = 0, = 0.3). The SMD of ARR after treatment and before treatment in the fingolimod group was - 1.3, (95% CI: -1.94, -0.65) (I = 97.4%, < 0.001). Conclusions: The results of this systematic review show that efficacy of interferon and fingolimod in controlling relapse rate and disability is similar.